Numerical and RSM Analysis of Hybrid CNT Nanofluid and Heat Transfer over a Moving Wedge Under Hydromagnetic Effects - Samat, Nazrul Azlan Abdul; Bachok , Norfifah; Arifin , Norihan Md (Journal of Quality Measurement and Analysis, 2026)
This study presents a mathematical and statistical analysis of hybrid carbon nanotube (CNT) nanofluid flow in the boundary layer across a wedge, emphasising the optimisation of heat transfer rates under the influence of hydromagnetic effects. The novelty of the study lies in the integrated use of Response Surface Methodology (RSM) to statistically maximise the thermal performance of this complex hybrid fluid system (single- and multi-walled CNTs in water), offering practical design parameters that extend beyond a numerical simulation. Using the bvp4c numerical method to solve the transformed ordinary differential equations (ODEs), we found that increasing the wedge and magnetic parameters significantly enhances both skin friction and heat transfer coefficients. Furthermore, the RSM analysis, optimised via the desirability function, successfully identified the best heat transfer conditions, concluding that the CNT volume fraction is the most influential factor and that the hybrid CNT nanofluid is superior to its mono-CNT counterpart for efficient heat transfer applications.